THE IMPACTS OF STUDENTS’ PERCEPTION ON TEACHING STYLE AND CLASSROOM CLIMATE TOWARDS STUDENTS OF SMP MUHAMMADIYAH SURUH’S LEARNING MOTIVATION IN 2017 - Ida Zahara Adibah (Universitas Muhammadiyah Semarang, 2018)
Teachers' teaching styles are varied depending on teacher's creativity to create an interesting teaching-learning process. The use of variations in teaching is needed to overcome the boredom experienced by students in the learning process in the classroom, so that students have the motivation to learn. Student's learning motivation can also be generated from school atmosphere or classroom climate. If students have felt comfortable with a conducive classroom climate, there will be feed backin the form of behavior, one of which is the increase in student's learning motivation. This study aims to determine the effect of students' perceptions of teachers' teaching styles and school climate, eitherpartially or simultaneously, on student's learning motivation. This research includes explanatory research with survey approach. The population in this study is all students of SMP MUHAMMADIYAH SURUH Year 2017 and the the sample is obtained by using the technique